Enhancing creative problem-solving in Thai undergraduate education: The creative flipped classroom model - Kongpiboon, Watcharin; Sovajassatakul, Thanongsak; Petsangsri, Sirirat (Edelweiss Applied Science and Technology, 2025)
This study developed and validated a technology-enhanced flipped classroom framework, the CREATIVE Model, to enhance undergraduate students' creative problem-solving skills (CPSS). The CREATIVE Model, based on constructivist and constructionist learning theories, employed several digital platforms to promote active and collaborative learning. The study also examined students' academic achievement (AA) and CPSS when taught under the CREATIVE Model compared to traditional instruction. Using a research and development (R&D) design, the suitability of the CREATIVE Model was validated by seven experts. Subsequently, the model was implemented among 65 undergraduate students enrolled in a Digital Photography Technology Course, selected through cluster random sampling. The participants were divided into an experimental group (n=35) and a control group (n=30). The research instruments included (1) lesson plans based on the CREATIVE Model, (2) a multiple-choice achievement test with four options, and (3) a CPSS rubric. Data analysis involved descriptive statistics and one-way MANOVA. Results indicated that the lesson plans were rated as highly suitable (M = 4.45, SD = 0.74). Additionally, there was a statistically significant difference in students' AA and CPSS scores between the experimental and control groups, with the CREATIVE Model group scoring higher on both measures at the .05 significance level. The findings confirm that the CREATIVE Model effectively enhances undergraduate students' academic achievement and creative problem-solving skills.